Pelatihan Alat Permainan Edukatif Bermuatan Moderasi Beragama di PAUD: Meningkatkan Pemahaman Toleransi Sejak Dini - Purwasih, Wahyu; Ariyani, Dewi; Ma'rufah, Desi Wijayanti (PELITA NUSA TENGGARA, 2025)
Educational Game Tools Training Containing Religious Moderation in PAUD: Increasing Understanding of Tolerance from an Early Age. This service began with the lack of integration of religious moderation values ​​in educational game tools in PAUD institutions. The main problem is the weak understanding and awareness of educators regarding the values ​​of religious moderation. The purpose of implementing this service activity is to provide training in making educational game tools that contain religious moderation. The location of the service activity is at TK Aisyiyah IV Purwokerto, Banyumas Regency. The service method used is the service learning method. The service provider provides services in the field of education. The initial steps taken by the service provider are to map the problems of the assisted subjects through interviews and focus group discussions, determine the activity plan to be carried out, initial assistance, religious moderation seminars, training in making teaching materials containing religious moderation, training in making educational game tools containing religious moderation. The results of this service activity are: (1) Increasing educator awareness of the use of educational game tools; (2) Increasing educator skills in making educational game tools containing religious moderation; (3) Increasing educator abilities in using educational game tools containing religious moderation. Pengabdian ini berawal dari kurangnya pengintegrasian nilai-nilai moderasi beragama dalam alat permainan edukatif di lembaga PAUD. Masalah utamanya adalah pada lemahnya pemahaman dan kesadaran pendidik mengenai nilai-nilai moderasi beragama. Tujuan pelaksanaan kegiatan pengabdian ini adalah untuk memberikan pelatihan pembuatan alat permainan edukatif yang bermuatan moderasi beragama. Lokasi kegiatan pengabdian bertempat di TK Aisyiyah IV Purwokerto Kabupaten Banyumas. Metode pengabdian yang digunakan menggunakan metode service learning. Pengabdi melakukan layanan pada bidang pendidikan. Langkah awal yang dilakukan pengabdi ialah melakukan pemetaan masalah subjek dampingan melalui wawancara dan focus group discussion, penetapan rencana kegiatan yang akan dilakukan, pendampingan awal, seminar moderasi beragama, pelatihan pembuatan bahan ajar bermuatan moderasi beragama, pelatihan pembuatan alat permainan edukatif bermuatan moderasi beragama. Hasil dari kegiatan pengabdian ini adalah: (1) Meningkatnya kesadaran pendidik akan pemanfaatan alat permainan edukatif; (2) Meningkatnya keterampilan pendidik dalam pembuatan alat permainan edukatif yang bermuatan moderasi beragama; (3) Peningkatan kemampuan pendidik dalam penggunaan alat permainan edukatif yang bermuatan moderasi beragama.